First Description of a New Disease in Rainbow Trout (Oncorhynchus mykiss (Walbaum)) Similar to Heart and Skeletal Muscle Inflammation (HSMI) and Detection of a Gene Sequence Related to Piscine Orthoreovirus (PRV) - Olsen, Anne Berit; Hjortaas, Monika; Tengs, Torstein; Hellberg, Hege; Johansen, Renate (PloS one, 2015)
In fall 2013, anorexia, lethargy and mortalities up to 10-12,000 dead fish per week were observed in rainbow trout Oncorhynchus mykiss in three fresh water hatcheries (salinity 0-1 ‰) on the west coast of Norway. The fish (25-100 g) showed signs of circulatory failure with haemorrhages, ascites and anaemia. The histopathological findings comprised inflammation of the heart and red muscle and liver necrosis. The affected fish had a common origin. Disease and mortalities were also observed up to four months after sea water transfer. Microbiological examination did not reveal presence of any known pathogens. Based on histopathological similarities to heart and skeletal inflammation (HSMI) in Atlantic salmon, associated with piscine orthoreovirus (PRV), extended investigations to detect a virus within the family Reoviridae were conducted. By the use of primer sets targeting the PRV genome, a sequence with 85% identity to a part of segment S1 of PRV was obtained. Further analysis showed that the virus sequence could only be aligned with PRV and no other reoviruses both on amino acid and nucleotide level. Two PCR assays were developed for specific detection of the virus. High amounts of the virus were detected in diseased fish at all affected farms and low amounts were detected in low prevalence at the broodfish farms. Further investigations are needed to determine if the virus is associated with the new disease in rainbow trout and to further characterize the virus with respect to classification, relationship with PRV, virulence, pathology and epidemiology.